O papel da criatividade na formação do futuro professor nos cursos de Pedagogia - Silveira, Pryscila Gianotti (2024)
The present research aims to understand students' perspectives on creativity in education and investigate whether, and how, teacher education programs in Pedagogy address the concepts of creativity in their courses. Throughout their academic training, students are given the opportunity to acquire theoretical and practical knowledge, aiming for their qualifications as teachers. The focus of this research on Higher Education arises from the question about the adequacy of this training, for understanding and promoting creativity in the aforementioned courses. The theoretical framework was composed from the contributions of GUILFORD (1950), TORRANCE (1965), ALENCAR (1986) and TORRE (1989), added to an in-depth research on the references to creativity present in the National Common Curricular Base (BNCC), by This is the guiding document for the basic schooling process, in which teaching activities need to be based, to ensure that the objectives outlined in that document are met. To achieve the proposed objectives, qualitative research was carried out, in which data were produced through a discussion group, composed of students in the seventh and eighth semester of Pedagogy, from university courses with face-to-face and distance learning (E.A.D) modalities. , located in São Paulo. Two categories were created for analysis and discussion. The results showed that, despite adequate understanding of the concept of creativity, the creative experiences experienced by the participants predominantly originate from professional activities or experiences during internships, demonstrating that there is a need to explore creativity in their education. However, even through the reports, it is possible to affirm that teachers in training are not instructed on how to interpret and apply creativity in their pedagogical practices